From hand to eye: the role of literacy, familiarity, graspability, and vision-for-action on enantiomorphy - Tânia Fernandes (2013)
Literacy in a script with mirrored symbols boosts the ability to discriminate mirror images, i.e., enantiomorphy. In the present study we evaluated the impact of four factors on enantiomorphic abilities: (i) the degree of literacy of the participants; (ii) the familiarity of the material; (iii) the strength of the association between familiar objects and manipulation, i.e., graspability; and (iv) the involvement of vision-for-action in the task. Three groups of adults - unschooled illiterates, unschooled ex-illiterates, and schooled literates - participated in two experiments. In Experiment 1, participants performed a vision-for-perception task, i.e., an orientation-based same-different comparison task, on pictures of familiar objects and geometric shapes. Graspability of familiar objects and unfamiliarity of the stimuli facilitated orientation discrimination, but did not help illiterate participants to overcome their difficulties with enantiomorphy. Compared to a baseline, illiterate adults had the strongest performance drop for mirror images, whereas for plane rotations the performance drop was similar across groups. In Experiment 2, participants performed a vision-for-action task; they were asked to decide which hand they would use to grasp a familiar object according to its current position (e.g., indicating left-hand usage to grasp a cup with the handle on the left side, and right-hand usage for its mirror image). Illiterates were as skillful as literates to perform this task. The present study thus provided three important findings. First, once triggered by literacy, enantiomorphy generalizes to any visual object category, as part of vision-for-perception, i.e., in visual recognition and identification processes. Second, the impact of literacy is much stronger on enantiomorphy than on the processing of other orientation contrasts. Third, in vision-for-action tasks, illiterates are as sensitive as literates to enantiomorphic-related information. (C) 2012 Elsevier B.V. All rights reserved.